As especificidades das práticas educativas na creche: o que as crianças expressam em suas vivências na educação infantil? - Winterhalter, Diolinda Franciele (2015)
The main goal of this dissertation is to understand the peculiarities of educational practices with infants and young children from what they express through different languages, considering the registers of the educational policy, National Curriculum Guidelines for Early Childhood Education - DCNEI as curricular proposal reference. Specifically, the research focused in observing day to day ways of interaction between children and educators, children and children from birth to three years old, children and the institutional collective environment in a Municipal School of Early Childhood Education; analyze educational practices developed with infants and young children; and from this, it was sought out to identify specificities for educational practices according to the needs / desires expressed by infants and young children through the different languages. Supported by the theoretical framework of childhood pedagogy and by authors who propose to think about education in the early years of life in a contemporary perspective such as Oliveira-Formosinho (2007; 2013); Richter and Barbosa (2010); Oliveira (2010); Barbosa (2010) proposed the insertion of two nursery classes, through participant observation and research-intervention method. Field diary register and day to day experience filmings were used as data production tools, in which analysis was performed throughout all the research. As the results of this study, we present the peculiarities of social practices such as eating, personal hygiene and sleep produced as educational practices in the indissociability of educating and taking care of babies and young children, the characteristics and the teaching roles as paying attention to the different languages, planning, organization of spaces, mediation of interactions and games such as specificity of the work / teachers / infants and young children; and specificity of spaces and environments for babies and small children in kindergarten as an opportunity of direct interventions with children, the organization of different spaces and discovery of different objects for interaction and games.